Modeling Underlying Pattern Making Construction Safety Risk Mitigation Decisions Using Dynamic Systems - Aswan Munang; Isnaini Nurisusilawati (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
The Occupational Health and Safety Management System (SMK3) is one of the factors that must be always monitored during the implementation of construction in achieving the success of project objectives. The implementation of SMK3 and decision-making still comes from project actors with different levels of experience gaps, causing the decisions taken to be less systematic and affecting the productivity of project performance. The purpose of the research is to conduct risk management simulations to increase insight into risk management and mitigation as a support for appropriate decision making in supporting project productivity, quality, and cost.Risk identification process through brainstorming, interviews, and observations with competent resource persons and project actors who have more than 5 years of experience in railway projects. Risk identification generates parameters and measures project risk by processing data using SPSS V23 software and dynamic simulation using Vensim PLE software. Simulation shows that there is a decrease in risk parameters in design and technology by -6.29%, construction management -5,12%, work safety and environment -5,90%, materials and equipment 3,37% and logistics -6,23%. Management of SMK3 by combining methods can increase accuracy in making risk mitigation decisions and can improve and understand the complexity of overall risk management performance from time to time.